Study on astaxanthin accumulation by heterotrophic transformation in Haematococcus pluvialis - ZHANG Rui-qin; GUAN Bin; KONG Qing; YOU Yong; WU Ji-qin; WEI Qun (浙江大学学报. 农业与生命科学版)
The effects of heterotrophic transformation and autotrophic transformation on astaxanthin production in Haematococcus pluvialis were studied and compared. When sodium acetate was added in MCM for heterotrophic transformation, astaxanthin accumulation was increased from 0.723 6 mg·L-1 to 1.216 8 mg·L-1. To enhance the astaxanthin accumulation, single factor experiment was founded up. Center composite design experiments and response surface methodology were employed to optimize the media of heterotrophic transformation. The results showed a distinctive influence of sodium acetate and potassium nitrate concentrations on astaxanthin accumulation. The optimal fermentation medium consisted of 1.460 5 g·L-1 sodium acetate, 0.008 4 g·L-1 potassium nitrate, and 0.02 g·L-1 potassium dihydrogen phosphate. Astaxanthin content reached 10.908 mg·L-1, which was raised 10.16-fold against the control group and 14.07-fold against the group of autotrophic transformation.